KEEFEKTIFAN LKPD BERBASIS LITERASI MATERI SISTEM PERNAPASAN PADA MANUSIA UNTUK MENINGKATKAN HASIL BELAJAR - Putri Ainur Rohmah; Laily Rosdiana; Aris Rudi Purnomo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2020)
This study aims to produce student worksheet based on effective human respiratory system material literacy. The subjects of this study were 33 grade VIII students of SMPN 3 Sidoarjo. This type of research was a quantitative descriptive study, One Group Pretest and Posttest Design. Effectiveness was determined by the results of the pretest, posttest and N-gain. The results showed that learning using student worksheet based on literacy is effective and can improve student learning outcomes. Effectiveness was reviewed from the learning outcomes obtained based on an increase in n-gain of 0.73 with a high category. The effectiveness results showed that 54.54% of students gained high n-gain score and 45.45% received medium n-gain score. For summing up, student worksheet based on scientific literacy is said to be effective and can improve learning outcomes and can be used in the learning process.